PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL PROBLEM BASED LEARNING UNTUK MENGEMBANGKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK PADA MATERI BANGUN RUANG SISI LENGKUNG KELAS IX SMP/MTs - Apriyani Apriyani; Sehatta Saragih; Yenita Roza (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research based on the limited learning instrument of mathematics as supporting learning in the Curriculum 2013. This research aims to develop the learning instruments such as syllabus, Lesson Plans (LP) and Student Worksheets (SW) based on 2013 Curriculum with the model of Problem Based Learning to develop student’s mathematical problem solving ability on curved sides space objects for 9th grade students of Junior High School. The procedure of research development was done based on 4-D model developed by Thiagarajan, Semmel and Semmel. This research was conducted from define step to develop step due to the lack of time and cost. The learning instrumen compiled was validated by three validators and revised based on the suggestions of validators. The researcher conducted two trials for a small group on 9 students of of class VIII SMP IT Al-Fityah Pekanbaru and a large group on 19 students of class VIII B Al-Fatih SMP IT Al-Fityah Pekanbaru to find out students’ responses to the use of SW. Based on the data analysis, it was be obtained that the average number of syllabus, LP, SW is 3.71, 3.62, 3.73 in a very valid category. Based on the trial result of small scale for SW, it was obtained that SW developed had fulfilled practicality requirement with an average percentage of 95.09%. The trial result of large scale obtained the average percentage of 94.67% and it had fulfilled practicality requirement.Keywords: Validity and Practicality, Research and Development, Problem Based Learning,Curved Sides Space